Possibilidades e Desafios: Turismo no Parque Natural Municipal da Gruta, Americana, SP, Brasil / Possibilities and Challenges: Tourism in Gruta Municipal Natural Park, Americana, São Paulo, Brazil - Ortolano, Fábio; Pereira da Silva Netto, Joviniano (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2016)
O presente artigo tem como objetivo construir um panorama teórico e programático para o desenvolvimento do ecoturismo no Parque Natural Municipal da Gruta, em Americana, Estado de São Paulo. Busca-se, assim, desvelar um cenário de potencialidades turísticas no município diante de um contexto político-econômico promissor ao desenvolvimento e planejamento público das atividades turísticas em âmbito estadual. Contudo, repleto de desafios locais na proteção e promoção de seus instrumentos urbanos e atrativos voltados ao lazer. Por meio de uma pesquisa-ação, foi articulado junto ao poder público um Fórum de Turismo e Desenvolvimento Local e, por meio da participação na formação de uma associação em prol do Parque, foram organizadas algumas ações de sensibilização e promoção da unidade de conservação, como a disponibilização de 300 registros fotográficos nas redes sociais. Disto, destaca-se a necessidade de ações emergenciais como a recuperação dos biomas originais e, consequentemente, dos processos ecológicos; a construção de instalações ecoturísticas; o tombamento do Parque junto aos órgãos competentes e um estudo sobre pertencimento da população, de modo que tais intervenções confiram às potencialidades do Parque uma vocação para a prática do turismo com ênfase no lazer e na memória, sendo referência para o município. PALAVRAS-CHAVE : Turismo. Produção do Turismo. Parque Natural Municipal da Gruta. Americana, SP. This article aims to build a theoretical and programmatic outlook for the development of ecotourism in the Municipal Natural Park Cave in Americana, state of São Paulo. It seeks, therefore, to unveil a scenario of tourism potentials in the face of a political and economical promising development and public planning of tourist activities in the state. However, full of local challenges in the protection and promotion of its instruments and urban attractions aimed at leisure. By means of an action research, was pleading with the public a forum for tourism and local development and, through participation in the formation of an association for the children, were organized some actions to raise awareness and promote the conservation unit. However, full of local challenges in the protection and promotion of its instruments and urban attractions aimed at leisure. By means of an action research, was pleading with the public a forum for tourism and local development and, through participation in the formation of an association for the children, were organized some actions to raise awareness and promote the conservation unit. Were performed more than 300 photographic records that are shared on social networks, to give visibility to the attractive and attention to their protection. This highlights the need for emergency actions such as the recovery of biomes originals and, consequently, of ecological processes; the construction of recreational ecotourism; the tipping of the park next to the competent bodies and a study on belonging of the population, so that such interventions confer the potential of the park a vocation for the practice of tourism with emphasis in leisure time and in memory, being a reference to the municipality. KEYWORDS : Tourism. Tourism Organizing. Gruta Municipal Natural Park. Americana, SP, Brazil. Fábio Ortolano - Doutorando em Psicologia Social, Instituto de Psicologia, Universidade de São Paulo, São Paulo, SP. Brasil. Currículo: http://lattes.cnpq.br/3286184609393257 E-mail: fabio.ortolano@usp.br Joviniano Pereira da Silva Netto - Doutorando em Geografia Humana, Faculdade de Filosofia, Letras e Ciências Humanas, Universidade de São Paulo, São Paulo, SP, Brasil. Currículo: http://lattes.cnpq.br/5415374947094280 E-mail: joviniano@usp.br